The long term prognostic value of peak left atrial strain in cardiac transplant patients. (4th February 2022) - Appadurai, V; Chamberlain, R; Edwards, NFA; Mulligan, A; Platts, D; Hamilton-Craig, C; Chan, J; Scalia, GM
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Left atrial (LA) dysfunction is associated with poorer outcomes in many disease processes. Left atrial strain (LAS) is a novel two-dimensional (2D) quantitative analysis of LA function. Cardiac transplantation directly involves the LA during implantation of the donor heart. Traditional echocardiographic indices after transplantation have demonstrated value in correlating with acute cellular rejection (ACR), morbidity and mortality over short- and long-term follow-up. The prognostic value of LA strain has not been previously investigated in this cohort. Purpose: We hypothesized that incrementally impaired LA strain in post cardiac transplant patients with varying degrees of ACR may be prognostic of poorer outcomes on long term follow-up. Methods: 87 Heart transplant patients, assessed between 2009 and 2015, underwent transthoracic echocardiography and endomyocardial biopsy. 2D strain analysis on the LV and LA were performed along with traditional echocardiographic parameters. Patients were grouped according to peak LAS (PALS) tertiles and rejection burden history was assessed and grouped according to ACR burden at a median of 12 (±5.4) months post transplantation. The primary endpoint was all-cause mortality at follow-up. Results: 12 patients met the primary endpoint over a median follow-up of 66 ± 51 months. The mean LA PALS was significantly different across the tertiles (lowest tertile 12.29 ± 2.5% vs middle tertile 17.89 ± 1.1% vs highest tertile 24.54 ± 4.2%; p <0.0001). LA strain dispersion was also significantly different between the tertiles (61.03 ± 25.8ms vs 41.8 ± 15.8ms vs 44.8 ± 18.8ms; p <0.001). All other clinical and echocardiographic parameters were non-significant between the tertiles however, there was a trend towards a lower PALS in the higher rejection burden group. Kaplan Meier curves demonstrated that survival over follow-up was significantly worse in the lower tertile LA PALS group compared to the highest tertiles LA PALS group (Log-rank test = p < 0.0001). The lowest LA PALS tertile had a significantly higher risk of reaching the primary endpoint compared with patients in the highest LA PALS tertile (hazard ratio [HR] 9.802; 95% CI 1.832-52.45; p <0.008). Higher LA PALS and LV GLS (LA PALS HR 0.610 95% CI 0.401-0.926; p 0.02; LV GLS HR 0.638 95% CI 0.418-0.972; p 0.037) were significantly associated with a reduction in reaching the primary endpoint in a multi-variate regression model including clinically relevant traditional and strain-based echocardiographic parameters. Conclusions: Lower LA PALS is significantly associated with poorer long-term outcomes in cardiac transplant patients with ACR. Non-invasive LA PALS may be a useful predictor of long-term outcome in patients post cardiac transplantation.